THE MODERATING EFFECT OF CEO DUALITY ON THE RELATIONSHIP BETWEEN RESEARCH AND DEVELOPMENT INVESTMENTS AND FIRM VALUE OF COMPANIES LISTED ON THE STOCK EXCHANGE OF THAILAND - Chaisomkun, Buncha (Journal of Liberal Arts and Management Science Kasetsart University, 2025)
Investment in Research and Development (R&D) is a high-risk strategy but essential for creating long-term corporate value. It is interesting to find out the key factors that drive complex and long-term R&D projects to success and create added value for the business. This study aims to examine the role of CEO duality in moderating the relationship between research and development (R&D) expenditures and firm value in companies listed on the Stock Exchange of Thailand (SET) during 2021 – 2023. The samples in this study were 384 firms. Secondary data was collected from the SETSMART database and analyzed using ordinary least squares (OLS) regression. The study found that R&D expenditures have a statistically significant positive impact on firm value. Furthermore, CEO duality acts as a positive moderator in the relationship between R&D expenditure and Firm Value of Companies listed on the Stock Exchange of Thailand. This study supports the perspective of Stewardship Theory, indicating that CEO duality is a strength that fosters unity of command and a clear strategic vision. This structure enables complex and high-risk investment decisions, such as those in R&D expenditures, to be made swiftly, thereby effectively enhancing organizational value.